Investigating the antibiotic resistance pattern of uropathogenic Escherichia coli isolated from urinary tract infections in outpatients referred to Kashan Reference Laboratory during 2021-2022 - Yasin Kalantari; Azad Khaledi; Maede Najafizade; Gholam Abbas Mousavi; Iman Saffari (مجله علوم پزشکی فیض (پیوسته))
Background and Aim: Understanding the antibiotic resistance profile of uropathogenic Escherichia coli in urinary tract infections (UTIs) across different populations and regions is crucial for appropriate antibiotic prescribing practices. This study aimed to assess the antibiotic resistance pattern of uropathogenic Escherichia coli isolated from UTIs in outpatients, focusing on gender and age demographics. Methods: This cross-sectional study analyzed 7365 urine culture samples obtained from patients consecutively referred to the Kashan Reference Laboratory between April 2021 and March 2022. Following sterile urine collection, bacterial cultures were grown on McConkey agar, blood agar, and specific media. Escherichia coli isolates were identified, and antibiotic resistance was determined using the disk diffusion method on Mueller Hinton agar, following National Committee for Clinical Laboratory Standards guidelines. Results: Among 401 positive urine cultures, 251 (62.5%) were attributed to E. coli, while 150 (37.4%) were related to other organisms. Of the E. coli cases, 226 isolates (90%) were from women and 25 (10%) from men. The E. coli strains exhibited the highest resistance (54.7%) to cefazolin and the lowest resistance (4.4%) to imipenem and nitrofurantoin. Antibiotic resistance in E. coli from men exceeded that of women across all antibiotics tested, with statistically significant differences observed in ceftriaxone, imipenem, ciprofloxacin, and nitrofurantoin (P<0.05). Additionally, antibiotic resistance in E. coli increased significantly in individuals aged 65 years and older compared to younger age groups, particularly in imipenem, ciprofloxacin, and cotrimoxazole (P<0.05). Conclusion: Male gender and old age are identified as risk factors associated with heightened antibiotic resistance in UTIs caused by E. coli. Clinicians should consider these factors when selecting empirical therapy for UTIs before culture results are available, especially in men and older patients. Reevaluation of prescribing practices for ceftriaxone in men and ciprofloxacin in men and the elderly is recommended due to elevated levels of antibiotic resistance.